EFFECTIVENESS OF SLOW DEEP BREATHING ON DECREASING BLOOD PRESSURE IN PRIMARY HYPERTENSION: A RANDOMIZED CONTROLLED TRIAL OF PATIENTS IN ATAMBUA, EAST NUSA TENGGARA - Berek, Pius A; Nurachmah, Elly; Gayatri, Dewi (MATTER: International Journal of Science and Technology, 2015)
SDB is a no pharmacology therapy applied to reduce blood pressure in patients with primary hypertension. The purpose of this study was to determine the effectiveness of slow deep breathing exercise to reduce blood pressure in patients with primary hypertension in Atambua, East Nusa Tenggara. The study was a quantitative research employing a randomized controlled trial design with pretest and posttest control group. The total number of the respondents was 142 including 33 respondents from the LS group, 37 respondents from the SDB group, 39 respondents from the combination of SDB-LS group, and 33 respondents from the control group. The results showed that there were differences in the reduction of systolic blood pressure between SDB group accounting for 28.59 mmHg and diastolic blood pressure accounting for 16.92 mmHg. The result of Anova analysis showed that there was a significant decrease on average of systolic blood pressure (P value = 0.002) and diastolic blood pressure (P value = 0.007). This research suggests the application of non-pharmacological actions particularly toward SDB exercise in order to decrease the prevalence of hypertension. This will minimize consequences caused by this problem.